Self‐management of lower urinary tract symptoms in post‐prostatectomy cancer patients: Content analysis. Issue 3 (28th June 2022) - Amano, Koji; Suzuki, Kumi
Abstract: What are the experiences of post‐prostatectomy cancer patients regarding self‐management of lower urinary tract symptoms? Individuals with prostate cancer are required to self‐manage their post‐operative lower urinary tract symptoms and issues associated with them. Clarifying the various aspects of self‐management can help in improving patient‐tailored support. This study therefore aimed to clarify the self‐management of lower urinary tract symptoms in prostate cancer patients who underwent total prostatectomy. Most post‐prostatectomy cancer patients have multiple lower urinary tract symptoms. They have a reduced quality of life due to the symptoms and associated physical, psychological, and social issues. Self‐management of the symptoms in uncomplicated cases has been shown to be effective, but this has not been clarified for post‐prostatectomy cancer patients. The study setting consisted of two designated cancer centres. A survey with semi‐structured interviews was conducted among 13 patients with prostate cancer that underwent total prostatectomy. Data were analysed using the qualitative content analysis techniques of Mayring. A total of 410 codes were extracted from which 42 subcategories and 10 categories emerged. The categories were: (1) recognition of issues associated with lower urinary tract symptoms to be solved; (2) examination of strategies for coping with these symptoms; (3) incorporation of actions that lead to an improvement in the symptoms; (4) avoidance of behaviours that cause worsening of the symptoms; (5) devising ways to prevent interference with one's daily life; (6) dealing with problems associated with the symptoms; (7) building relationships with medical staff and surroundings; (8) self‐evaluation of bladder control status; (9) positive acceptance of the symptoms; and (10) sensing the effectiveness of strategies regarding the control of urination. The results suggest that health care professionals need to provide feedback to patients on LUTS strategies and their effects to help support patient coping strategies. In addition, determining individual patients' strengths and deficiencies in self‐management will allow us to tailor assistance to patients. This is the first step towards the development of self‐management scales to objectively assess self‐management.